Methods of coping with stress and its relationship to the quality of family life to a sample of mothers of deaf and hard of hearing children in the western region of the Kingdom of Saudi Arabia - Almaghrabi, Dhuha Omar (Journal of Educational and Psychological Sciences, 2023)
This study aims to identify the methods of coping with psychological stress and its relationship to the quality of family life among mothers of deaf and hearing impaired in the western region of the Kingdom of Saudi Arabia. The descriptive correlative approach has been used to suit the research objectives. The sample was 314 mothers. The researcher also used the scale of methods of coping with psychological stress among families of people with special needs prepared by Al-Zahrani (2019), as well as the scale of the quality of family life for “families with special needs” prepared by Abdel Wahab (2016). The study concluded that the most used methods of coping with psychological stress among the sample are the positive methods, foremost of which are (religiosity- problem solving). There were also differences on the scale of methods of coping with stress due to the economic level in favor of the economic level (less than 4000) and the level (8000 to less than 12000) in the method of religiosity, differences due to the educational level in favor of the educational level (graduate studies) and differences attributed to the sex of the affected child in favor of females' mothers in the style of (social support- problem solving- cognitive construction). Moreover, it concluded that there is an average level of the quality of family life for mothers of deaf and hearing-impaired, and there are differences attributed to the economic level in favor of the high economic level in the dimension of physical happiness/physical health.
Keywords: Coping; Stress; Quality of life; Deaf mothers